NEURONS AND THEIR STRUCTURE (The New Uzbekistan Journal of Medicine, 2025)
This article discusses the structure, types and functional differences between neurons. The main parts of a neuron — soma, dendrites and axons — are analyzed along with their functions. Information is also provided about the process of information exchange between neurons, that is, the transmission of impulses and the role of synapses. The article reveals the role of neurons in the nervous system and their importance in controlling the activity of the organism. This material may be useful for those interested in biology, anatomy and neurology.